15. The Effect of Celery (Apium graveolens L.) Leaf Infusion on Blood Cholesterol Levels in White Male Rat (Rattus norvegicus) Induced by Alloxan - Kiky Moelviani; Sugito Sugito; Roslizawaty Roslizawaty; Zuhrawati NA; Rusli Rusli; T. Armansyah TR (Jurnal Medika Veterinaria, 2019)
This study aimed to determine the effect of celery (Apium graveolens L.) leaves infusion on blood cholesterol levels in male rats (Rattus norvegicus) induced by alloxan. The sample used in this study were 25 white male rats Wistar strained aged 3-4 months with a bodyweight of 150-200 grams. The design used are were unidirectional pattern of completely randomized design with 5 treatments and 5 replications. Treatment 1 (P1) rats  were given with the standard feed. Treatment 2 (P2),rats  were induced by alloxan. Treatment 3 (P3) rats were induced by alloxan and given 2 ml of 5% celery leaf infusion therapy. Treatment 4 (P4) rats  were induced by alloxan and given 2 ml of 10% celery leaf infusion therapy. Treatment 5 (P5) rats  were induced by alloxan and given 2 ml of 15% celery leaf infusion therapy. Celery leaf infusion was given every morning and evening. Administration of  alloxan with a single dose of 150 mg / kg in  IP and celery leaf infusion therapy were given for 14 days. Rat blood cholesterol levels checked using the CHOD-PAP. Data were analyzed using ANOVA completely randomized design. Mean (± SD) of cholesterol in treatment P1, P2, P3, P4 and P5 sequence was 52.8 ± 9.09; 50.4 ± 18.53; 42.6 ± 4.51; 40.2 ± 52.8 ± 7.19 and 2.39. The results showed that the infusion of celery leaves was not showing any effect (P 0.05) on blood cholesterol levels of white male rats induced by alloxan. Administration of celery leaves (Apium graveolens L.) infusion for 14 days with a concentration of 5%, 10% and 15% have no effect on blood cholesterol levels in male rats induced by alloxan.